2012
DOI: 10.1128/jb.06711-11
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analyses Reveal Overall Topology and Functional Regions of NilB, a Bacterial Outer Membrane Protein Required for Host Association in a Model of Animal-Microbe Mutualism

Abstract: The gammaproteobacterium Xenorhabdus nematophila is a mutualistic symbiont that colonizes the intestine of the nematode Steinernema carpocapsae. nilB (nematode intestine localization) is essential for X. nematophila colonization of nematodes and is predicted to encode an integral outer membrane beta-barrel protein, but evidence supporting this prediction has not been reported. The function of NilB is not known, but when expressed with two other factors encoded by nilA and nilC, it confers upon noncognate Xenor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 56 publications
6
63
0
Order By: Relevance
“…Further study revealed that this locus is not present in other Xenorhabdus bacterial symbionts and is sufficient to confer colonization of S. carpocapsae on naturally non-colonizing bacteria, establishing for the first time a genetic element conferring host range expansion in an animal-bacterial association (Cowles and Goodrich-Blair, 2008). nilB is similar to genes found in animal associated microbes, including mucosal pathogens (Heungens et al , 2002; Bhasin et al , 2012), supporting the idea that common molecules or mechanisms maintain many host-bacterial interactions regardless of whether the outcome of the interaction is mutualistic or pathogenic (McFall-Ngai et al , 2010). The function of NilB, a surface exposed outer membrane protein (Bhasin et al , 2012) remains unclear, but analysis of the EPN symbiont genome sequences has provided some clues.…”
Section: 'Omic' Insights Into Nematode-bacterial Mutualismsupporting
confidence: 60%
See 1 more Smart Citation
“…Further study revealed that this locus is not present in other Xenorhabdus bacterial symbionts and is sufficient to confer colonization of S. carpocapsae on naturally non-colonizing bacteria, establishing for the first time a genetic element conferring host range expansion in an animal-bacterial association (Cowles and Goodrich-Blair, 2008). nilB is similar to genes found in animal associated microbes, including mucosal pathogens (Heungens et al , 2002; Bhasin et al , 2012), supporting the idea that common molecules or mechanisms maintain many host-bacterial interactions regardless of whether the outcome of the interaction is mutualistic or pathogenic (McFall-Ngai et al , 2010). The function of NilB, a surface exposed outer membrane protein (Bhasin et al , 2012) remains unclear, but analysis of the EPN symbiont genome sequences has provided some clues.…”
Section: 'Omic' Insights Into Nematode-bacterial Mutualismsupporting
confidence: 60%
“…nilB is similar to genes found in animal associated microbes, including mucosal pathogens (Heungens et al , 2002; Bhasin et al , 2012), supporting the idea that common molecules or mechanisms maintain many host-bacterial interactions regardless of whether the outcome of the interaction is mutualistic or pathogenic (McFall-Ngai et al , 2010). The function of NilB, a surface exposed outer membrane protein (Bhasin et al , 2012) remains unclear, but analysis of the EPN symbiont genome sequences has provided some clues. Relaxed search parameters revealed that each of the four sequenced genomes of EPN symbionts, including X. nematophila itself, encodes a NilB-like protein in a conserved genomic context.…”
Section: 'Omic' Insights Into Nematode-bacterial Mutualismsupporting
confidence: 60%
“…To create low-and high-Lrp-expressing X. nematophila strains, pMYC4 (low-lrp donor plasmid) and pMYC5 (high-lrp donor plasmid) were inserted into the kefA gene of an lrp-2::kan mutant via biparental conjugation and homologous recombination, respectively. Plasmid integration at the kefA gene locus does not interfere with nematode colonization (4,16,56,57). The Lrp-dependent fluorescence reporter pMYC1 (PfliC-gfp/P lac -rfp) was introduced into the attTn7 site of the genomes in both of the low-Lrp-and high-Lrp-expressing X. nematophila strains described above by triparental conjugation and Tn7 transposition (58,59), creating low-lrp in-genome (low-lrp/Tn7-PfliC-gfp/P lac -rfp) and high-lrp in-genome (high-lrp/Tn7-PfliC-gfp/P lac -rfp) strains.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of relevant plasmids are listed in Table 2. All of these plasmids have been successfully used in either Xenorhabdus or Photorhabdus bacteria in association with their nematode host 14,17,20,24,[33][34][35] . To ensure stable maintenance of the fluorescent protein during nematode colonization it is best to use a plasmid that will insert into the chromosome of the target bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…This is an advantage over other methods of monitoring bacteria within nematode populations, such as sonication 22 or grinding 23 , which can provide average levels of colonization, but may not, for example, discriminate populations with a high frequency of low symbiont loads from populations with a low frequency of high symbiont loads. Discriminating the frequency and load of colonizing bacteria can be especially important when screening or characterizing bacterial mutants for colonization phenotypes 21,24 . Indeed, fluorescence microscopy has been used in high throughput screening of bacterial mutants for defects in colonization 17,18 , and is less laborious than other methods, including sonication 22,[25][26][27] and individual nematode dissection 28,29 .…”
mentioning
confidence: 99%